Patient-Centered Care Models in Primary Healthcare: A Systematic Review of Implementation and Outcomes - Alsagoor , Hussin Mahdi Saleh; Alsagoor, Mana Mahdi Hassan; Fadhil , Sultan Hamad Binali Al; Almushraaf, Abdulaziz Saleh Hamad; Almansour, Ali Mohammed Ali; Alqawban, Saleh Mohammed Hussain; Al atiq, Ahmad Qublan Hassan; Alghubari, Fahad Mahdi Mohammed; Alyami, Mohammed Mahdi Hassan; Algahes, Marzoug Mubarak (Journal of Ecohumanism, 2024)
This systematic review evaluates the implementation and outcomes of patient-centered care (PCC) models in primary healthcare settings. Patient-centered care is a foundational approach in primary healthcare, emphasizing patient preferences, needs, and values to improve the quality of care and health outcomes. A comprehensive literature search was conducted across PubMed, Cochrane, and MEDLINE databases, focusing on studies that assessed the impact of PCC models such as the Patient-Centered Medical Home (PCMH) and shared decision-making. Forty studies met the inclusion criteria, covering a range of patient populations and healthcare settings. Findings indicate that PCC models enhance patient satisfaction, improve health outcomes, and increase patient engagement in care. Additionally, these models positively impact provider satisfaction and may reduce healthcare costs by lowering emergency visits and hospitalizations. However, challenges in implementation, including provider workload and resource needs, were commonly reported. This review underscores the effectiveness of PCC models in primary care and highlights the need for structured, resource-supported implementation strategies. Further research is recommended to optimize PCC approaches across diverse populations and healthcare systems.